Problems for the Purported Cognitive Penetration of Perceptual Color Experience and Macpherson’s Proposed Mechanism - Steven Gross; Thitaporn Chaisilprungraung; Elizabeth Kaplan; Jorge Aurelio Menendez; Jonathan Flombaum (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Fiona Macpherson (2012) argues that various experimental results provide strong evidence in favor of the cognitive penetration of perceptual color experience. Moreover, she proposes a mechanism for how such cognitive penetration occurs. We argue, first, that the results on which Macpherson relies do not provide strong grounds for her claim of cognitive penetrability; and, second, that, if the results do reflect cognitive penetrability, then time-course considerations raise worries for her proposed mechanism. We base our arguments in part on several of our own experiments, reported herein.
Keywords: perceptual color experience; cognitive penetration; color perception